Teacher Efforts to Overcome Student Learning Difficulties in Islamic Religious Education Subjects - Muhammad Ridho Abdul Rozaq; Muhibbin Syah; Bambang Samsul Arifin; Ahmad Subarna (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research is motivated by the number of students who still have difficulty learning in PAI subjects. The purpose of this study was to determine the teacher's efforts in overcoming student learning difficulties in PAI subjects. This study uses a qualitative method of descriptive approach by conducting observations, interviews and document studies. The results and conclusions of this study, teachers make efforts to overcome learning difficulties by building trust, strong communication, making PAI learning fun and meaningful, increasing students' understanding and ability by explaining the material, increasing the motivation of students' enthusiasm for learning and increasing competence and self professionalism.